Disruption of Transverse-Tubules Eliminates the Slow Force Response to Stretch in Isolated Rat Trabeculae - Power, Amelia; Kaur, Sarbjot; Dyer, Cameron; Ward, Marie-Louise (Frontiers in Physiology, 2020)
Ventricular muscle has a biphasic response to stretch. There is an immediate increase in force that coincides with the stretch which is followed by a second phase that takes several minutes for force to develop to a new steady state. The initial increase in force is due to changes in myofilament properties, whereas the second, slower component of the stretch response (known as the ‘slow force response’ or SFR) is accompanied by a steady increase in Ca2+ transient amplitude. Evidence shows stretch-dependent Ca2+ influx during the SFR occurs through some mechanism that is continuously active for several minutes following stretch. Many of the candidate ion channels are located primarily in the t-tubules, which are consequently lost in heart disease. Our aim, therefore, was to investigate the impact of t-tubule loss on the SFR in non-failing cardiac trabeculae in which expression of the different Ca2+ handling proteins was not altered by any disease process. For comparison, we also investigated the effect of formamide detubulation of trabeculae on β-adrenergic activation (1 µM isoproterenol), since this is another key regulator of cardiac force. Measurement of intracellular calcium ([Ca2+]i) and isometric stress were made in RV trabeculae from rat hearts before, during and after formamide treatment (1.5 M for 5 min), which on washout seals the surface sarcolemmal t-tubule openings. Results showed detubulation slowed the time course of Ca2+ transients and twitch force, with time-to-peak, maximum rate-of-rise, and relaxation prolonged in trabeculae at optimal length (Lo). Formamide treatment also prevented development of the SFR following a step change in length from 90% to 100% Lo, and blunted the response to β-adrenergic activation (1 µM isoproterenol).